Migration, kinship, and community : tradition and transition in a Spanish village - Brandes, Stanley H. (Studies in social discontinuity., 1975)
Migration, Kinship, and Community: Tradition and Transition in a Spanish Village analyzes the nature and impact of depopulation on a small peasant village in southwestern Castile, called Becedas. This book discusses the migration and peasant society, population and life style, village economy, family and household, and ritual and social structure of Becedas. An overview of the village and region of Becedas are also described, focusing on the geographical, economic, and political forces which helped to shape the peasant village's way of life. This publication is a good source for students and researchers concerned with the modernization and economic development of traditional peasant people, structure and composition of the peasant community, and relationship between the peasant community and the outside world.